2004
DOI: 10.1073/pnas.0402089101
|View full text |Cite
|
Sign up to set email alerts
|

Localized chemical release from an artificial synapse chip

Abstract: A device that releases chemical compounds in small volumes and at multiple, well defined locations would be a powerful tool for clinical therapeutics and biological research. Many biomedical devices such as neurotransmitter-based prostheses or drug delivery devices require precise release of chemical compounds. Additionally, the ability to control chemical gradients will have applications in basic research such as studies of cell microenvironments, stem cell niches, metaplasia, or chemotaxis. We present such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 25 publications
0
67
0
Order By: Relevance
“…Development is rapid, both on the hardware side, where multielectrode recordings from more than 300 electrodes permanently implanted in the brain are currently state-of-the art, and on the software side, with computers learning to interpret the signals and commands (Nicolelis et al 2003;Shenoy et al 2003;Carmena et al 2003). Early experiments on humans have shown that it is possible for profoundly paralyzed patients to control a computer cursor using just a single electrode (Kennedy and Bakay 1998) implanted in the brain, and experiments by Parag Patil and colleagues have demonstrated that the kind of multielectrode recording devices used in monkeys would most likely also function in humans (Peterman et al 2004;Patil et al 2004). Experiments in localized chemical release from implanted chips also suggest the possibility of using neural growth factors to promote patterned local growth and interfacing (Peterman et al 2004).…”
Section: Brain-computer Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Development is rapid, both on the hardware side, where multielectrode recordings from more than 300 electrodes permanently implanted in the brain are currently state-of-the art, and on the software side, with computers learning to interpret the signals and commands (Nicolelis et al 2003;Shenoy et al 2003;Carmena et al 2003). Early experiments on humans have shown that it is possible for profoundly paralyzed patients to control a computer cursor using just a single electrode (Kennedy and Bakay 1998) implanted in the brain, and experiments by Parag Patil and colleagues have demonstrated that the kind of multielectrode recording devices used in monkeys would most likely also function in humans (Peterman et al 2004;Patil et al 2004). Experiments in localized chemical release from implanted chips also suggest the possibility of using neural growth factors to promote patterned local growth and interfacing (Peterman et al 2004).…”
Section: Brain-computer Interfacesmentioning
confidence: 99%
“…Early experiments on humans have shown that it is possible for profoundly paralyzed patients to control a computer cursor using just a single electrode (Kennedy and Bakay 1998) implanted in the brain, and experiments by Parag Patil and colleagues have demonstrated that the kind of multielectrode recording devices used in monkeys would most likely also function in humans (Peterman et al 2004;Patil et al 2004). Experiments in localized chemical release from implanted chips also suggest the possibility of using neural growth factors to promote patterned local growth and interfacing (Peterman et al 2004).…”
Section: Brain-computer Interfacesmentioning
confidence: 99%
“…The concept mentioned above has been advanced by Peterman et al (2004) and Takoh et al (2005). They developed a porous membrane-based substrate to provide localized chemical release of substances to cultured cells via a microfluidic interface from below.…”
Section: Introductionmentioning
confidence: 99%
“…Intercellular communications of cardiac myocytes cultured on porous polycarbonate membranes (Takoh et al 2005) were detected by observing cytosolic Ca 2C transients using fluo-4. The same detection method was employed to observe repeated stimulation of PC12 cells with bradykinin (Peterman et al 2004). In these experiments, the PC12 cells were cultured on silicon nitride membranes integrated into silicon chips.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic dosing devices have been introduced that enable selective stimulation of cells and study of cell membrane receptors and pathways [1][2][3][4][5][6]. Patterned laminar flows confined by polymer or glass microchannels demonstrate the microfluidic control of cell inactivation with cellular and sub-cellular resolution [1,4,5].…”
Section: Introductionmentioning
confidence: 99%